Educação literária e a formação docente: encontros e desencontros do ensino de literatura na escola e na Universidade do Século XXI - Segabinazi, Daniela Maria (2011)
The main goal of this doctoral dissertation is to discuss the pedagogical education of literature professors in universities: their methodologies and conceptions regarding literature teaching. This research focuses on literature teacher education in Letras Course at UFPB, aiming at discussion and analysis of literature teaching in Letras Courses and its relationship with elementary education. It also highlights public policies and the history of literature teaching since its beginnings in Brazilian education, in order to understand and analyze literature teacher education in Letras Graduate Course at UFPB. Having this issue in mind, we raised questions about literature teacher education and its correlation with high schools and started our doctoral dissertation. We adopted literature and field research as our methodology, the last one consisting in students and teachers in high schools and undergraduates and professors in Letras Course. At first we set the discussion starting from a historical course of legislation and reforms which instituted the teaching of literature in schools and universities, pointing to the main changes and the permanence of some models in current teaching. After that, we investigated literature teaching in high school and higher education from theoretical approaches and, mainly, from data collected through questionnaires applied to students and teachers of both levels. We found that literature teaching in universities is limited to the History of Literature and reading of literary canon. Consequently this structure is reproduced in the contents and methodologies of high school literature teachers. We also found that the bibliography is recurring and there is no discussion regarding the didactics of literature and its correlation with high school in Letras Undergraduate Course at UFPB. Professors implement little or no change in their syllabuses and even after the curricular changes in the Pedagogical Project (PPP) of Letras Course they know little about the Curricular Guidelines of teacher education. It was also possible to detect that the same happens with high school teachers, reflecting a vicious circle in literature teaching.